Quasi-Periodic (QP) ELF-VLF Emissions Observed in High Latitudes - Sato, Natsuo (1980)
P(論文) The characteristics of quasi-periodic (QP) ELF-VLF emissions with periods of 3-150 s and their relationships to magnetic pulsations are studied by using data obtained from Syowa and Mizuho Stations in Antarctica and Husafell in Iceland which is located near the geomagnetic conjugate point of Syowa Station. From the relations of QP emissions to magnetic pulsations, QP emissions are classified into two types, Type 1 and 2 QP emissions, according to whether the emissions are clearly associated with magnetic pulsations or not. The typical characteristics of Type 1 QP emissions are as follows. The intensity and period of QP emissions change concurrently with variations in the intensity and period of magnetic pulsations. From the coherency analysis between QP emissions and Pc 3-4 magnetic pulsations it is found that the coherency between the D component of magnetic pulsations and the intensity fluctuations of QP emissions is much higher than that between the H component of magnetic pulsations and QPs. It is also found that the propagation time of magnetic pulsations (HM waves) from the interaction region between magnetic pulsations and QPs in the magnetosphere to the ground is 20-30 s. These properties are observed at conjugate-pair stations with good conjugacy. The results strongly suggest that Type 1 QP emissions are modulated by compressional mode Pc 3-4 magnetic pulsations near the equatorial plane in the outer magnetosphere. On the other hand, QP emissions are categorized as the Type 2 QP emissions when the period of concurrent pulsations is entirely different from that of QP emissions or the amplitude of pulsations is too small to determine the periodicity. The most striking feature of Type 2 QP emissions are their very regular periodicity as compared with that of Type 1 QP emissions, and the Q value of the spectral peak usually attains to more than 10. In most cases magnetic variations during Type 2 QP events, which occur under magnetically quiet condition, have no spectral peak corresponding to the ...